2013
DOI: 10.1177/0093854813510911
|View full text |Cite
|
Sign up to set email alerts
|

A Firesetting Offense Chain for Mentally Disordered Offenders

Abstract: Relatively little effort has been made to develop and validate theories that explain firesetting.In this study the first offense chain model of firesetting in mentally disordered offenders was developed. Twenty-three mentally disordered firesetters were interviewed about the affective, cognitive, behavioral and contextual factors leading up to and surrounding one of their recorded firesetting offenses. Offense account interviews were analysed using groundedtheory. The resulting model consists of four main phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 34 publications
(46 reference statements)
2
43
0
Order By: Relevance
“…However, motive has been extensively examined within the numerous typological classifications of firesetting behaviour (see Gannon & Pina, ). Within the DMAF, eight offence goals were reported in line with existing findings: revenge (Lewis & Yarnell, ), economic gain (Barker, ), thrill‐seeking (Icove & Estepp, ), communication (Canter & Fritzon, ), crime concealment (i.e., a criminal problem in the DMAF; Inciardi, ), vandalism (i.e., thrill‐seeking in the DMAF; Inciardi, ), protection (Tyler et al ., ), and protest (Rix, ). Revenge , in line with the literature, was found to be the most prominent offence goal, accounting for a third of the sample (see Barnoux & Gannon, for a review).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, motive has been extensively examined within the numerous typological classifications of firesetting behaviour (see Gannon & Pina, ). Within the DMAF, eight offence goals were reported in line with existing findings: revenge (Lewis & Yarnell, ), economic gain (Barker, ), thrill‐seeking (Icove & Estepp, ), communication (Canter & Fritzon, ), crime concealment (i.e., a criminal problem in the DMAF; Inciardi, ), vandalism (i.e., thrill‐seeking in the DMAF; Inciardi, ), protection (Tyler et al ., ), and protest (Rix, ). Revenge , in line with the literature, was found to be the most prominent offence goal, accounting for a third of the sample (see Barnoux & Gannon, for a review).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the development of Tyler et al . 's () model represents a significant milestone in current firesetting theory, it is limited to offenders who were formally diagnosed with a mental health disorder at the time of the fire. Further, reliability checks were not employed in order to ensure strong levels of accuracy, reliability, and validity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an earlier study, we developed an offence chain model that outlined the offence process for firesetting in mentally disordered offenders— the Firesetting Offence Chain for Mentally Disordered Offenders (FOC-MD; Tyler et al, 2013). The FOC-MD was developed using qualitative research methods (i.e., grounded theory) and describes the offence process for male and female mentally disordered firesetters in a temporal sequence, based on offenders’ narratives of their offences.…”
mentioning
confidence: 99%
“…This finding suggests that the specific sessions within the FIP‐MO aimed at targeting interest, attitudes, and beliefs about fire and fire safety awareness were effective in reducing deficits in these areas for treatment participants. Further, anger has been reported in the literature as a common emotion experienced by firesetters (Barnoux, Gannon, & Ó Ciardha, ; Gannon et al, ; Green, Lowry, Pathé, & McVie, ; Tyler et al, ), and aggressive motives are consistently reported as being highly prevalent for firesetting (Ritchie & Huff, ; Rix, ). Thus, it is encouraging that male and female firesetters who completed the FIP‐MO showed significant improvements in their self‐reported ability to express their anger relative to the comparison group.…”
Section: Discussionmentioning
confidence: 99%